Birch and spruce trees on the north bank of the Kuskokwim River, Alaska, September 1914 - University of Washington Libraries. Special Collections Division.
Caption under photo: Birch & Spruce covered Ridges N. bank Kuskokwim. McPherson number: K453 PH Coll 495.2-43d Photograph from album created in circa 1914 by James Lennox McPherson, a civil engineer, that documents the activities of the Kuskokwim Reconnaissance survey party (known as Party No. 11 of the Alaska Railroad Commission expedition). The A.E.C. had assigned McPherson to research the feasibility of building a branch railroad from Anchorage west to the mining districts on the Kuskokwim and Iditarod Rivers.